(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study was carried out to describe the current situation of occupational burnout among medical staff at the Department of Surgery-Anesthesiology and Resuscitation (SAR), Hung Vuong Hospital in 2023. Methods: This was a cross-sectional design study. The sample size for quantitative research is all 155 medical staffs currently working at the Department of SAR. Data were collected using Maslach’s scale (MBI-HSS 22 questions). Results: The overall rate of medical staff with signs of occupational burnout was 62.5% (high level was 33.5%, average level was 29.0%); Occupational burnout was most common in the aspect of emotional exhaustion (62.6%), personal achievement (56.1%), and lastly, depersonalization (41.3%). The rate of high levels of burnout was more common in men, work experience <10 years, on duty >6 times/month, working time >48 hours/week and overtime (p<0.05). Conclusion: There is a need to increase awareness of the role of mental health among medical staff and ways to handle and overcome stress. Set up rest areas, arrange work appropriately and increase extracurricular activities for medical staff.